Knowledge, attitude and practices about menstruation and related problems in adolescent girls - Sultan, Shabana; Sahu, Deep Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Menstruation and menstrual practices are still clouded by taboos and socio-cultural restrictions resulting in adolescent girls remaining ignorant of the scientific facts and hygienic health practices, which sometimes result into adverse health outcomes. The reaction to menstruation depends upon awareness and knowledge about the subject. The manner in which a girl learns about menstruation and its associated changes may have an impact on her response to the event of menarche. Department of Obstetrics and Gynecology, Bhopal, India had always been keen to make aware of these facts and preventive measures to adolescent girls and to acknowledge the facts this study has been conducted. Methods: About 350 school girls between 10-18years of age with attainment of menarche were selected from two schools of Bhopal and interviewed during study period using predesigned questionnaire after obtaining informed consent from school in-charge and parents. Results: This study shows that majority of the girls preferred cloth pieces rather than sanitary pads as menstrual absorbent. Apparently, poverty, high cost of disposable sanitary pads and to some extent ignorance dissuaded the study population from using the menstrual absorbents available in the market. Universalized use of sanitary pads can be advocated to every girl only by making it available at affordable prices (social marketing). Thus, the above findings reinforce the need to encourage safe and hygienic practices among the adolescent girls and bring them out of traditional beliefs, misconceptions and restrictions regarding menstruation. Conclusions: This study highlighted the need of adolescent girls to have accurate and adequate information about menstruation and its appropriate management and healthy menstrual practices.